2014
DOI: 10.1038/ncomms4950
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced role of eddies in the Arctic marine biological pump

Abstract: The future conditions of Arctic sea ice and marine ecosystems are of interest not only to climate scientists, but also to economic and governmental bodies. However, the lack of widespread, year-long biogeochemical observations remains an obstacle to understanding the complicated variability of the Arctic marine biological pump. Here we show an early winter maximum of sinking biogenic flux in the western Arctic Ocean and illustrate the importance of shelf-break eddies to biological pumping from wide shelves to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 46 publications
6
133
1
Order By: Relevance
“…The difference in chlorite and sedimentation rate records between 01A-GC and 05JPC/06JPC may be related to either (1) variable sediment focusing at different water depths or (2) redistribution of the BSI water between different branches after passing the Bering Strait. (1) A sediment-trap study demonstrated that shelf-break eddies in winter are important to carry fine-grained lithogenic material from the Chukchi shelf to the slope areas (Watanabe et al, 2014). This redeposition process may have weakened the BSI signal in slope sediments of 05JPC/06JPC compared with outer-shelf sediments of 01A-GC.…”
Section: Holocene Changes In the Bering Strait Inflowmentioning
confidence: 99%
“…The difference in chlorite and sedimentation rate records between 01A-GC and 05JPC/06JPC may be related to either (1) variable sediment focusing at different water depths or (2) redistribution of the BSI water between different branches after passing the Bering Strait. (1) A sediment-trap study demonstrated that shelf-break eddies in winter are important to carry fine-grained lithogenic material from the Chukchi shelf to the slope areas (Watanabe et al, 2014). This redeposition process may have weakened the BSI signal in slope sediments of 05JPC/06JPC compared with outer-shelf sediments of 01A-GC.…”
Section: Holocene Changes In the Bering Strait Inflowmentioning
confidence: 99%
“…Submesoscale physical features are especially important to biogeochemical processes affecting the horizontal and vertical distribution of nutrients and phytoplankton biomass [Watanabe et al, 2014]. Most of the participating models are developed on global scales and only four of them are regional models of the order of 10 km resolution (Table 1).…”
Section: 1002/2016jc011993mentioning
confidence: 99%
“…1). Early-winter maxima of sinking particle flux with fresh organic material have been captured annually at Station NAP (75 • N, 162 • W, 1975 m water depth) (Watanabe et al, 2014;. The substantial quantities of lithogenic minerals in the trapped particles suggest shelf-origin water transport toward the NAP region.…”
Section: E Watanabe Et Al: Wind-driven Interannual Variability Of Smentioning
confidence: 96%
“…Further detailed investigation of the background mechanisms associated with summer biogenic flux would be highly valuable and possible using a coupled physical and marine ecosystem model. Whereas the main content of observed diatom valves was the sea ice-related species (e.g., Fossula arctica, , the sea ice ecosystem was not included in our previous model experiment (Watanabe et al, 2014). The lack of ice algae was a plausible factor for the summer delay of the simulated biogenic flux peak behind the trap data.…”
Section: E Watanabe Et Al: Wind-driven Interannual Variability Of Smentioning
confidence: 96%
See 1 more Smart Citation